The Human Element: Self-Regulated Learning Skills and Strategies Though Role-modelling and Guided Mastery - Merino, Andres; Aucock, Michele (South African Journal of Higher Education, 2016)
This article explores the experiences of a black male student as he undertook a challenging academic journey through high school and university to the completion of a four year degree in Accountancy. Data were collected by means of three in-depth, semi-structured interviews which were then analysed to identify the key themes that shaped the student’s academic journey. Two distinct cycles of failure followed by success emerged from the analysis of the data. In both cases, through the role-modelling and guided mastery of Self-Regulated Learning strategies and skills by a few committed and dedicated persons, the student was able to develop academic resilience and achieve his goals. Drawing on the findings of the case study, the authors identify some of the challenges faced by students from educationally disadvantaged backgrounds within the present day South African context, and suggest possible solutions through the adoption of Self-Regulated Learning and the principles and practices of Guided Mastery. Keywords Self-regulated learning, motivation, role-modelling, guided mastery, academic resilience, accounting education.